Management of corporate culture development - Li Weixin (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of the research: the development and impact of FAW-VW’s corporate culture on its growth and sustainability in the Chinese automotive industry.is the corporate culture of FAW-Volkswagen, focusing on its development course from inception to its current state, examining how this culture has influenced the company’s management practices, employee behavior, and market performance. Subject of the research: the in-depth analysis of FAW-VW’s corporate culture framework, including its mission, vision, core values, corporate spirit, and business policies, and their influence on employee behavior, management practices, and overall performance.is the analysis of the establishment, evolution, and impact of FAW-Volkswagen’s corporate culture. It involves understanding the internal mechanisms that shaped the culture, external influences from both Chinese and German corporate practices, and how the corporate culture aligns with FAW-Volkswagen’s strategic goals.
Scientific advisor: Cherniavska I., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; corporate culture; value orientations of employees; organizational goals; development management